Mobile-Based Dine-In Self-Ordering Application with QR Code - Tan, Gui Mei; Sahadun, Nur Afiqah (Applied Information Technology And Computer Science, 2026)
Online food ordering systems have become a revolutionary approach to replace traditional methods by creating a contactless environment when taking orders in the food and beverage industry. Nevertheless, Lido Seafood Restaurant offers Chinese cuisine, which operates its business using a paper-based menu and Genius POS System with the waitstaff's assistance, which may cause delays during peak time, especially lunchtime. As a result, an online self-ordering system with a QR code is developed to transform the ordering services in their restaurants. The system was built using the waterfall methodology, developed in VS Code, with Android Studio used for SDK and emulator setup, also Flutter and Dart. It integrates Firebase Authentication, Firebase Hosting, Firebase Firestore, Cloudinary, and Curlec (by Razorpay). Customers scan QR code to order via mobile while the administrator manages menus, orders, and payments through the dashboard. Overall, the system enhances customer satisfaction and boosts dine-in efficiency.